Leadership and work motivation from the cross cultural perspective - Mohd. Israil, Khaliq Ahmad (Emerald Group Publishing Limited, 2009)
Purpose – The purpose of this paper is to compare and contrast conventional management thought, its main features of leadership, and work motivation with those from an Islamic perspective. The paper fills in the literature gap that exists, despite the growing importance of a need for knowledge on management from an Islamic perspective.